Biosynthesis and Chemopreventive Potential of Jute (Corchorus capsularis and C. olitorius) Flavonoids and Phylogeny of Flavonoid Biosynthesis Pathways - Satya, Pratik; Sarkar, Debabrata; Chatterjee, Amitava; Pal, Srikumar; Ray, Soham; Sharma, Laxmi; Roy, Suman; Bera, Amit; Ghosh, Srinjoy; Mitra, Jiban; Kar, Gouranga; Singh, Nagendra Kumar (Planta Medica International Open, 2022)
Flavonoids are valuable phytochemicals for human health and nutrition. Jute (Corchorus capsularis and C. olitorius), a vegetable rich in phenolics and flavonoids, is globally consumed for its health benefit, but the biosynthesis pathways and metabolic profiles of its flavonoids are poorly characterized. Elucidating the flavonoid biosynthesis pathways would augment the broader use of jute, including targeted synthesis of its specific flavonoids. We reconstructed the core flavonoid biosynthesis pathways in jute by integrating transcriptome mining, HPLC and flavonoid histochemistry. In C. capsularis (white jute), the flavonoid biosynthesis pathways’ metabolic flux was driven toward the biosynthesis of proanthocyanidins that mediate the acquisition of abiotic stress tolerance. However, higher levels of flavonols in C. olitorius (tossa jute) render it more suitable for nutritional and medicinal use. Jute flavonoid extract exhibited in vitro inhibition of matrix metalloproteinase-2, suggesting its potential chemopreventive and immunity-boosting roles. Using the flavonoid biosynthesis pathways profiles of 93 plant species, we reconstructed the flavonoid biosynthesis pathways phylogeny based on distance-based clustering of reaction paths. This reaction-path flavonoid biosynthesis pathways phylogeny was quite distinct from that reconstructed using individual gene sequences. Our flavonoid biosynthesis pathways-based classification of flavonoid groups corroborates well with their chemical evolution, suggesting complex, adaptive evolution of flavonoid biosynthesis pathways, particularly in higher plants.
Keywords: Corchorus spp.; flavonoid; Malvaceae; MMP-2; pathway; phylogeny